Characterization of the combining ability of maize inbred lines containing temperate germplasm using Striga‑resistant testers - Adekunle, D.; Mengesha Abera, W.; Abe, A.; Meseka, S.K.; Bunmi, B.; Menkir, A. (2025)
Temperate maize inbred lines are potential sources of desirable alleles for tropical germplasm improvement. To date, the benefit of the temperate inbred lines as a potential source of beneficial alleles for Striga hermonthica resistance breeding to enhance genetic gain in tropical maize has not been fully exploited. This study was conducted to define the heterotic resemblances of the temperate inbred lines using two tropical testers and determine the impact of the temperate inbred lines when used as a parent to improve economically important agronomic traits under normal and Striga infested conditions. Thirty-two temperate lines and two testers were crossed using line x tester mating design. The resulting 64 hybrids plus 4 checks were evaluated for two years using 17× 4 alpha lattice design with 2 replications under infested and non-infested conditions at Abuja and Mokwa in Nigeria. The mean performance of testcrosses for grain yield was generally higher under non-infested than under infested condition. Grain yield (GY) ranged from 1973.00–4714.00 kg/ha under Striga infested condition, and 1964.00–5428.00 kg/ha under non-infested condition. Ten temperate inbred lines had positive GCA effects for GY under both conditions and seventeen testcrosses had positive specific combining ability (SCA) for GY. There were significant mean square differences due to line GCA for days to 50% silking and days to 50% pollen shed and SCA of lines× tester interaction was significant for grain yield under Striga infestation, indicating that the performance of temperate lines in testcrosses varies with the testers. These results could facilitate systematic introgression of the temperate inbred lines into the existing Striga resistant heterotic groups in IITA. The temperate inbred lines with positive GCA effects and producing high grain yields in hybrid combinations could be useful parents for enhancing Striga resistance and agronomic performance of tropical maize germplasms.